Redescription of C. Willmann’s Holarctic species of the genus Trhypochthonius (Acari: Oribatida: Trhypochthoniidae) - Szywilewska-Szczykutowicz, Anetta; Olszanowski, Ziemowit (Zootaxa, 2007)
Trhypochthonius nigricans and T. cladonicolus are redescribed on the basis of type specimens originating from C. Willmann’s collection and comparative material from Poland, Canada and the USA. The taxonomic importance of some morphological characters is analysed. Shape of the sensillus does not seem to be a good diagnostic character in the genus Trhypochthonius. Trhypochthonius sphagnicolus is recognized as a junior synonym of T. nigricans and T. cladonicolus is noted for the first time from the North America.